Shared Margins An Ethnography with Writers in Alexandria after the Revolution - Schielke, Samuli (ZMO-Studien, 2021)
Shared Margins tells of writers, writing, and literary milieus in Alexandria, Egypt's second city. It de-centres cosmopolitan avant-gardes and secular-revolutionary aesthetics that have been intensively documented and studied since 2011. Instead, it offers a fieldwork-based account of various milieus and styles, and their common grounds and lines of division.